PENGARUH GERAKAN MEDIA SOSIAL DAN PARTISIPASI BOIKOT TERHADAP MINAT BELI PRODUK MCDONALD’S DI KALANGAN MAHASISWA SURABAYA - Farrel Fawaz Ziiqbal; Zumrotul Fitriyyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Israel's attacks on Palestine have impacted the global economy. Jewish products perceived as Israeli are boycotted in many countries, resulting in substantial losses. This phenomenon has spread to Indonesia. This study investigates the influence of social media and participation in boycott movements on the purchasing interest of McDonald's products among students in Surabaya. Boycotts against brands like McDonald's often arise in response to global political issues, particularly concerning conflicts in the Middle East, including controversies involving Israel. The study involves 100 students as respondents and utilizes Structural Equation Modeling (SEM) to analyze data. The research findings indicate that the influence of social media on McDonald's purchasing interest is not significant among Surabaya students. However, participation in boycott movements shows a strong and significant impact on their purchasing interest. These findings highlight that students often use boycotts as an expression of their values regarding politically sensitive global issues.